Heart Rate Variability, Risk-Taking Behavior and Resilience in Firefighters During a Simulated Extinguish-Fire Task - Prell, Rebecca; Opatz, Oliver; Merati, Giampiero; Gesche, Björn; Gunga, Hanns-Christian; Maggioni, Martina A. (Frontiers in Physiology, 2020)
Firefighters face a high-risk potential, thus their psychological ability to cope with critical or traumatic events is a crucial characteristic. This study examines correlations between cardiac autonomic modulation, risk-taking behavior, and resilience in professional firefighters. Twenty male professional firefighters underwent a 20 min beat-to-beat heart rate (HR) monitoring at baseline at morning upon awakening, then before, during and after a realistic deployment in a container, systematically set on fire. Risk-taking behavior, resilience and subjective stress were assessed by specific validated tools after deployment: the Risk-taking scale (R-1), the Resilience Scale (RS-13), and the multi-dimensional NASA-Task Load Index. The cardiac autonomic modulation at rest and in response to stress was assessed by classic indexes of heart rate variability (HRV) as RMSSD and LF/HF ratio. Results showed that: (i) risk-taking behavior correlated with a withdrawal in vagal indices, shifted the baseline sympathovagal balance toward sympathetic predominance (LF/HF ratio r(8)=0.522, p=.01), and increased HR mean both in baseline and during physical exercise (r(8)=0.526, p=.01 and r(8)=0.445, p=.05 respectively); (ii) resilience was associated with higher vagal indices (RMSSD r(18)=0.288, p=.04), and with a baseline sympathovagal balance shifted toward parasympathetic predominance (LF/HF ratio r(18)=-0.289, p=.04); (iii) the physical workload of firefighting led to a significantly increased mean HR (p=.002; +22 bpm, 95% CI [9.70, 35.82]) in comparison to the firefighters who did not exercise, which lasted in the recovery phase (p=.005 +24 bpm; 95% CI [8.62, 41.16]). Associations of risk-taking behavior and resilience with cardiac autonomic modulation could be demonstrated, showing that HRV may be a valuable monitoring tool in this specific population; however further studies are warranted for validation.